Giant condyloma acuminate due human papilloma virus type 16 in an infant successfully treated with topical imiquimod therapy - Dinleyici, Meltem; Saracoglu, Nurhan; Eren, Makbule; Kiliç Ömer; Ciftci, Evrim; Sag, Cigdem; Kara, Ates; Cagri Dinleyici, Ener (Dermatology Reports, 2015)
Anogenital warts related to human papillomavirus (HPV) have been observed in children. Definition of the transmission mode, therapy, and follow-up for long term potential complications is important. A 27-month old girl was admitted with multiple pedunculated red-purple colored cauliflower-like lesions of 1.5 years duration. Clinical/histopathological and microbiological diagnosis was condyloma acuminate due to HPV type 16. After 12 weeks of imiquimod 5% cream application (pea-sized) overnight three times per week, the perianal warts had completely disappeared. The mode of transmission of HPV 16 in our case was probably horizontal, related to the sharing of common personal hygiene items in the women’s shelter. We report herein the case of an infant living in a women’s shelter with giant condyloma acuminata due to HPV 16, which was successfully treated with topical imiquimod therapy. This patient should be followed up for recurrence and potential malignant lesions related to HPV type 16.